Hybrid energy of Photovoltaic and Palm Oil Diesel for alternative electricity supply of Base Transceiver Station (BTS) on rural Area-South Sumatera. Issue 4 (March 2021) - Basit, A; Sudiarto, B; Setiabudy, R
Abstract: The lack of electricity supply from PLN (The Indonesia State Electricity Enterprise) due to the remote and far geographical location, Some of the BTS rely on diesel generators as the main power plant. So, the cost of electricity generation in the BTS is very high because of the high cost of transportation of these fuels. Therefore, to make efficient use of diesel fuel requires a renewable energy-based power generation model by utilizing the natural potential around the area. This study to analyse the system models hybridization of Photovoltaic System with Palm oil Diesel (POD) to get power plants that have high reliability, low energy costs and low emissions for powering BTS in remote area located at a Sungai Ketupak Village of Ogan Komering Ilir-South Sumatera (Latitude 3o19.9'S and Longitude 105o38.9'E). The Hybrid Optimization Model for Electric Renewable Energy (HOMER) has been carried out to obtain an optimal design based on energy cost/kWh, annual operating costs, the daily loads demand, the NPV cost. The combination PV system and palm oil diesel will provide benefits for telecommunications companies in the savings for fuel generators. This system could also reduce gas emissions from hydrocarbon fuels. Therefore, the join of PV and palm oil diesel systems shows a good prospect of alternative energy for BTS tower energy sources.